2020
DOI: 10.1371/journal.pone.0238207
|View full text |Cite
|
Sign up to set email alerts
|

Unusual metastases from differentiated thyroid cancers: A multicenter study in Korea

Abstract: Background Although infrequent, distant metastasis from differentiated thyroid cancer is the main cause of mortality in patients and mostly involves the lung, bone, and brain. Distant metastases to other sites in differentiated thyroid cancer patients are rare, thus, the clinical course of unusual metastases has not been adequately researched. In the present study, the clinicopathological findings and treatment outcomes of unusual metastases in differentiated thyroid cancer patients in Korea were evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 36 publications
1
22
1
4
Order By: Relevance
“…Contrary to our report, only six patients of the latter group experienced lesions in more than one unusual metastatic site. Furthermore, most of these patients were diagnosed with PTC, and the median survival (68 months) was markedly inferior to the observed survival of our patient (more than 168 months) [ 13 ]. A meta-analysis by Paspala et al ., which included 11 patients with pancreatic metastases from thyroid carcinoma revealed an even worse median overall survival of only 37.6 months as opposed to the data presented in our report [ 22 ].…”
Section: Discussioncontrasting
confidence: 61%
See 3 more Smart Citations
“…Contrary to our report, only six patients of the latter group experienced lesions in more than one unusual metastatic site. Furthermore, most of these patients were diagnosed with PTC, and the median survival (68 months) was markedly inferior to the observed survival of our patient (more than 168 months) [ 13 ]. A meta-analysis by Paspala et al ., which included 11 patients with pancreatic metastases from thyroid carcinoma revealed an even worse median overall survival of only 37.6 months as opposed to the data presented in our report [ 22 ].…”
Section: Discussioncontrasting
confidence: 61%
“…In our patient, we observed metastases in different organs and soft tissue (that is, lung, heart, kidney, pancreas, and skeletal muscle) over a period of more than 14 years. Retrospective analyses have reported that 1–3% of all DTC display distant disease [ 13 , 18 ]. Although reports of patients experiencing more than three metastatic sites are scarce, Hugen et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Only sporadic reports are available on TA outcomes in liver metastases of other origins, including thyroid cancer. Use of LTA and RFA were described in single case-reports [90,91] as effective for rapid tumor burden decrease and associated with marked, but temporary, symptom improvement. Therefore, TA should be considered in a multimodality approach to DTC patients who are at surgical risk and in whom other treatment modalities are ineffective.…”
Section: Liver Metastasesmentioning
confidence: 99%